ANALYSIS OF THE SOCIAL AND PHILOSOPHICAL THEORIES OF HARMONIZING SOCIAL AND LEGAL EDUCATION (Scientific journal of the Fergana State University, 2024)
The article examines the scientific and methodological foundations for harmonizing social and legal education in Uzbekistan, the social and philosophical necessity of integrating social and legal education in the New Uzbekistan, and the prospects of social and legal education as a social necessity in the development of Uzbekistan. Additionally, it analyzes the social and philosophical theories related to the harmonization of social and legal education.